2013
DOI: 10.2460/javma.243.7.990
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and persistence of antimicrobial-resistant bacteria isolated from dogs and cats admitted to a veterinary teaching hospital

Abstract: Extended hospitalization was associated with increased risk of acquiring MDR E coli or MRSA, although few animals acquired MRSA. It is unclear whether associations were confounded by illness severity or use of infection control measures. Additionally, MRSA of ST5, which has been associated with small animal medicine, was the most commonly acquired MRSA in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
6
29
3
2
Order By: Relevance
“…Results from the simulations done with randomized parameter values and subsequent regression analyses suggest that the model is consistent with previous reports that the incidence of both resistant and non-resistant strain colonization increases with increasing length of stay in the hospital [14], [15], [33]. As long as the number of patients already hospitalized is below the maximum capacity for the hospital, longer patient stays contribute to a higher number of hospitalized patients, leading to more interactions between patients, healthcare workers and transmission points.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results from the simulations done with randomized parameter values and subsequent regression analyses suggest that the model is consistent with previous reports that the incidence of both resistant and non-resistant strain colonization increases with increasing length of stay in the hospital [14], [15], [33]. As long as the number of patients already hospitalized is below the maximum capacity for the hospital, longer patient stays contribute to a higher number of hospitalized patients, leading to more interactions between patients, healthcare workers and transmission points.…”
Section: Discussionsupporting
confidence: 86%
“…Risk-based case control studies have shown that hospitalization is a serious risk factor for dogs becoming rectal carriers of multi-drug resistant (MDR) E. coli [14], [15]. Dogs staying for over 6 days experience an increased risk of carrying MDR E. coli while those patients who had been hospitalized previously and/or had been treated with fluoroquinolones previously had higher probability of carrying MDR E. coli on arrival to the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Netherlands reported a high prevalence of faecal carriage of Enterobacteriaceae resistant to third-generation cephalosporins in cats and dogs (Hordijk et al, 2013). Various risk-based case control studies reported that hospitalization is a major risk associated with the dogs to become multi-drug resistant (MDR) E. coli rectal carriers (Gibson et al, 2011;Hamilton et al, 2013). Enterobacter cloacae, also a nosocomial agent and particularly the multidrug resistant strains, are concerning (Wilberger et al, 2012).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Veterinary hospitals are the major source and accountable for increasing prevalence of a MDR E. coli in horses (Ahmed et al, 2012). Veterinary personnel and veterinary hospital environments are allegedly most important key factors in risk of gaining antibiotic resistant pathogens by hospitalized dogs (Hamilton et al, 2013;Heller et al, 2010;KuKanich et al, 2012). …”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Pour autant, les infections nosocomiales enzootiques ne devraient pas être sous-estimées et la réalité des infections nosocomiales en médecine vétérinaire est probablement sous-estimée (Morley, 2013). Par ailleurs, plusieurs études ont démontré une association significative entre l'hospitalisation et le portage de bactéries multi-résistantes chez l'animal (Gibson et al 2011;Nienhoff et al 2011;Hamilton et al 2013).…”
Section: Fréquence Des Infections Nosocomiales Chez Les Animaux De Counclassified